14‐4: Invited Paper: A Diffractive LCD Backlight Approach to Dynamic Lightfield Displays. Issue 1 (May 2016) - Aieta, Francesco; Vo, Sonny; Ma, Ming; Niederberger, Armand; Fattal, David
Abstract : We introduce a novel approach to LCD backlighting that allows for the generation of dynamic lightfields through a single LCD panel. The backlight is based on diffractive nanostructures that are 90% transparent. Full control over the spatio‐angular parameters of the lightfield is achieved, providing new opportunities for the design of naked‐eye 3D displays, heads‐up displays and near‐eye Virtual / Augmented Reality systems.